Reframing Corporate Social Responsibility as a strategic instrument for poverty reduction and social welfare in Zanzibar - Bakari Khatib Faki (Privietlab, 2026)
Corporate Social Responsibility (CSR) has increasingly been viewed as something beyond a philanthropic act, but as a strategic means by which companies may contribute to sustainable development. CSR in Zanzibar is frequently centered in the service and tourism sectors, where projects are often restricted to a short-term act of charity, rather than a sustained impact. This article discusses CSR's potential as a poverty reduction tool and social welfare enhancement tool in Zanzibar. With a descriptive and analytical approach, employing secondary data from government reports, NGO sources, and case studies in private sector CSR projects, this paper explores CSR interventions' effectiveness. The findings indicate that although CSR projects in Zanzibar give very essential community infrastructure such as scholarships, health programs, and environmental conservation, their poverty reduction input is fragmented, not coordinated, and in need of systematic appraisal. The study posits adopting models such as the Plan-Do-Check-Act-Improve PDCAI cycle and models of participatory approach to development could make CSR a sustainable poverty reduction engine. By aligning CSR directly to social welfare, this piece shows its contribution toward discourse in private sector involvement in social inequalities remedy. Moreover, it gives policy advice toward effectively strengthening CSR governance, ensuring a community-led, sustainable Zanzibar social welfare outcome.